2020
DOI: 10.52547/ijrr.18.4.633
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of lung doses for radiation pneumonia risk in stereotactic body radiotherapy: A comparison of intensity modulated radiotherapy, intensity modulated arc therapy, cyberknife and helical tomotherapy

Abstract: The evaluation of lung doses for radiation pneumonia risk in stereotactic body radiotherapy: A comparison of intensity modulated radiotherapy, intensity modulated arc therapy, cyberknife and helical tomotherapy INTRODUCTIONNon-small cell lung cancer (NSCLC) covers 75 -80% of all lung cancer patients. Approximately 15-20% of patients are localized and early stage. Generally, the 5-year survival rate is 60-70% when surgical treatment is performed in these patients. However, a significant proportion of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The V20 is an important metric for IL in breast radiotherapy. Ipsilateral lung volume receiving ≥ 20 Gy (V20) is a predictor of radiation pneumonitis risk, therefore it is aimed to reduce the volume receiving 20 Gy [ 25 27 ]. When compared with HT, HTp significantly reduced V20 for IL, while on the contrary VMATp was found to have significantly increased it.…”
Section: Discussionmentioning
confidence: 99%
“…The V20 is an important metric for IL in breast radiotherapy. Ipsilateral lung volume receiving ≥ 20 Gy (V20) is a predictor of radiation pneumonitis risk, therefore it is aimed to reduce the volume receiving 20 Gy [ 25 27 ]. When compared with HT, HTp significantly reduced V20 for IL, while on the contrary VMATp was found to have significantly increased it.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported in many studies that irradiated heart and lung volumes and doses are associated with long-term morbidity and mortality (4)(5)(6)(7)(8) . It has also been reported that mean lung doses in breast cancer RT are associated with radiation pneumonia (9)(10)(11) . Studies conducted on US SEER cancer registries in patients who were irradiated for breast cancer from 1970 to early 1980 by the standard RT regimens at the time reported that deaths from heart disease and lung cancer were appreciably increased 10 to 20 years afterwards (4,5) .…”
Section: Introductionmentioning
confidence: 96%